Peningkatan Motivasi Belajar Siswa Pada Mata Pelajaran Ipas Melalui Penerapan Model Discovery Learning Pada Siswa Kelas Iv Sd Inpres Perumnas Antang I - Nurul Hidayah Suryadin (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to improve students' learning motivation in the subject of science through the application of the Discovery Learning model in the fourth grade of SD Inpres Perumnas Antang I. The study was conducted due to the low learning motivation of students characterized by passive behavior, lack of enthusiasm, and minimal active involvement of students during the learning process. The research method used was Classroom Action Research (CAR) which was carried out in two cycles with 29 fourth grade students as subjects. Data were collected through observation sheets on the implementation of the Discovery Learning model syntax, learning motivation questionnaires, interviews, and documentation. The results showed that the implementation of the Discovery Learning model syntax by teachers increased from 40.27% in the first cycle to 86.80% in the second cycle. Student learning motivation also increased from 58.30% in the first cycle to 88.17% in the second cycle, with 96.55% of students achieving a score of ≥75. Overall, the application of the Discovery Learning model was able to improve the learning motivation of fourth grade elementary school students in the subject of science.